DEVELOPMENT OF AESTHETIC EDUCATION IN EXTRACURRICULAR INSTITUTIONS OF UKRAINE (1954-1968) - O.A. Gudovsek (Academy of Cognitive and Natural Sciences, 2010)
In the article development of out-of-school establishments of aesthetically beautiful direction is exposed in 1954-1968.